Impact of Summer Monsoon on Urban Traffic Air Pollution Dispersion in Growing Tourism Destination: Case of Salalah, Oman - CHARABI, Yassine; Abdul-WAHAB, Sabah A.; CHOUDRI, B. S.; AL-RAWAS, Ghazi; AL-WARDY, Malik; FADLALLAH, Sulaiman (Journal of Environmental Management and Tourism, 2018)
Abstract : The paper concentrates on utilizing CALPUFF to model and investigate the impact of monsoon season on the dispersion of carbon monoxide (CO), carbon dioxide (CO2), and mononitrogen oxides (NOx) emitted from vehicles. The fact that during monsoon season, traffic jam has become an important matter in Salalah, Sultanate of Oman due to the rapid increase in Salalah visitors. The main aim is to evaluate the concentrations of CO, CO2, and NOx for the region during monsoon season and compare those levels of concentration with non-monsoon seasons by taking Salalah as an area source. CALPUFF simulation analysis was subdivided into two main parts: analysis according to the selected modeling days for both monsoon and non-monsoon seasons, and comparative analysis assessing the concentrations of CO, CO2, and NOx for the region during monsoon season and comparing those levels of concentration with non-monsoon seasons. For the first section of the analysis, the modeling periods' meteorological conditions were multifarious and as a result, concentration levels as well as the coordinates were concentrations exceeded the criterion limits differed. As for the second part of the analysis, the comparison revealed that concentration levels of CO, CO2, and NOx during monsoon season were greater than the levels associated with the modeling days during non-monsoon season. The increase in number of vehicles and the blowing wind from the south-eastern direction toward the region are the significant factors affecting the dispersion of vehicle pollutants within Salalah’s domain during monsoon season. To minimize traffic congestion, it is recommended to boost mass transit services in the region to encourage tourists to visit Salalah's favorable sights by public transportation instead of driving their own vehicles.